2020
DOI: 10.1002/alz.12130
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular vesicle biomarkers of Alzheimer's disease associated with sub‐clinical cognitive decline in late middle age

Abstract: Introduction: Neuronal extracellular vesicle (nEV) tau and insulin signaling biomarkers may detect preclinical Alzheimer's disease and age-associated cognitive decline. Methods: This case-control study used repeated serum samples from 73 cognitively declining and 73 stable Wisconsin Registry for Alzheimer's Prevention participants (62.4 ± 6.3 years old). We immunocaptured nEVs; measured tau and insulin signaling biomarkers; and examined biomarker differences by group, their performance in group classification … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 52 publications
3
42
1
Order By: Relevance
“…Zhao et al have demonstrated that the levels of DJ-1 and α-syn from neural-derived exosomes are significantly higher in PD patients' plasma than those of healthy people [70]. Furthermore, it has been shown that the levels of Aβ and tau in neuronal-derived exosomes are higher in AD patients' blood and greatly correlated with those in CSF [5,71]. Commercial kit and immunoprecipitation methods have been used to isolate the neuronal-derived exosomes in the blood.…”
Section: Potential Diagnostic Biomarkers Of Exosomes In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Zhao et al have demonstrated that the levels of DJ-1 and α-syn from neural-derived exosomes are significantly higher in PD patients' plasma than those of healthy people [70]. Furthermore, it has been shown that the levels of Aβ and tau in neuronal-derived exosomes are higher in AD patients' blood and greatly correlated with those in CSF [5,71]. Commercial kit and immunoprecipitation methods have been used to isolate the neuronal-derived exosomes in the blood.…”
Section: Potential Diagnostic Biomarkers Of Exosomes In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Firstly, brain-derived exosomes in peripheral blood have shown great potential to be an ideal "liquid biopsy" for AD (Table 1). Exosomes derived from blood are characterized by low invasive diagnostic procedures with high sensitivity and specificity [61]. Clinical diagnosis of AD depends on symptoms, neuropsychological testing, lumbar puncture, and neuroimaging [62,63].…”
Section: Role Of Exosomes In Admentioning
confidence: 99%
“…Next to Aβ, other products of the APP processing pathway (i.e., sAPPα and sAPPβ) are also increased in plasma NDEs from AD patients compared to controls [ 143 ]. Serum-derived NDEs isolated from older individuals with age-related cognitive decline milder than MCI or dementia also show higher pT231 Tau, pT181 Tau and t-Tau in comparison with age-matched cognitively stable individuals [ 148 ].…”
Section: Evs As Potential Biomarkers For Ad and Pdmentioning
confidence: 99%
“…However, in this sample set, the IRS-1-pTyr levels were significantly increased in preclinical AD patients as well [ 135 ]. Importantly, the levels of several insulin signaling mediators in serum-derived NDEs were shown to be associated with a longitudinal, prospective change in cognitive performance in a cohort of individuals with and without age-related cognitive decline [ 148 ]. The plasma NDE levels of several synaptic proteins and transcription factors mediating neuronal protection are significantly decreased in multiple AD stages (preclinical AD patients, MCI patients converting to AD, AD patients) compared to controls and stable MCI patients [ 75 , 138 , 139 , 140 , 141 ].…”
Section: Evs As Potential Biomarkers For Ad and Pdmentioning
confidence: 99%